Design and experiment of seeding performance monitoring system for suction corn planter - Liu, Kun; Yi, Shujuan (International Journal of Agricultural and Biological Engineering, 2019)
To realize the highly precise and real-time monitoring of seeding performance in suction-type corn planter, and intelligent detection technology was presented. In this monitoring system, firstly, the sensor was designed based on the photoelectric technology. Meanwhile, in order to reduce the influence of dust in the field on the photoelectric sensor, the installation position of the sensor was changed to the space under the seed plate instead of the traditional position, that is, the middle of the seed tube. Secondly, the scattering angle of the highlighting light-emitting diodes was considered to calculate the spacing of transmitters to realize non-blind area detection. Last but not least, the peak-detection algorithm was utilized to increase the detection accuracy. Therefore, after a lot of the indoor and field experiments, the analysis shows that the detection accuracy of seeding quantity can reach 98.45%, alarm delay time under abnormal circumstances is not more than 2 s. Obviously, this system can meet the requirements of seeding completely and improve its reliability greatly.Keywords: seeding performance, monitoring system, peak-detection algorithm, photoelectric detectionDOI: 10.25165/j.ijabe.20191204.4185Citation: Liu K, Yi S J. Design and experiment of seeding performance monitoring system for suction corn planter. Int J Agric & Biol Eng, 2019; 12(4): 97–103.